Cell-penetrating peptide–morpholino conjugates alter pre-mRNA splicing of DMD (Duchenne muscular dystrophy) and inhibit murine coronavirus replication in vivo. (20th July 2007) - Moulton, H.M.; Fletcher, S.; Neuman, B.W.; McClorey, G.; Stein, D.A.; Abes, S.; Wilton, S.D.; Buchmeier, M.J.; Lebleu, B.; Iversen, P.L.
Abstract : The cellular uptake of PMOs (phosphorodiamidate morpholino oligomers) can be enhanced by their conjugation to arginine-rich CPPs (cell-penetrating peptides). Here, we discuss our recent findings regarding (R-Ahx-R)4 AhxB (Ahx is 6-aminohexanoic acid and B is β-alanine) CPP–PMO conjugates in DMD (Duchenne muscular dystrophy) and murine coronavirus research. An (R-Ahx-R)4 AhxB–PMO conjugate was the most effective compound in inducing the correction of mutant dystrophin transcripts in myoblasts derived from a canine model of DMD. Similarly, normal levels of dystrophin expression were restored in the diaphragms of mdx mice, with treatment starting at the neonatal stage, and protein was still detecTable 22 weeks after the last dose of an (R-Ahx-R)4 AhxB–PMO conjugate. Effects of length, linkage and carbohydrate modification of this CPP on the delivery of a PMO were investigated in a coronavirus mouse model. An (R-Ahx-R)4 AhxB–PMO conjugate effectively inhibited viral replication, in comparison with other peptides conjugated to the same PMO. Shortening the CPP length, modifying it with a mannosylated serine moiety or replacing it with the R9 F2 CPP significantly decreased the efficacy of the resulting PPMO (CPP–PMO conjugate). We attribute the success of this CPP to its stability in serum and its capacity to transport PMO to RNA targets in a manner superior to that of poly-arginine CPPs.